Trust and transformation in the water sector in South Africa - Goldin, Jaqui (Department of Political Studies, 2014)
Water policy under the 1956 Water Act actively discouraged participation and water was managed centrally. The principles enshrined in the National Water Act (no 36 of 1998), designed in line with international sustainable development goals that actively encourage participation of a wide range of stakeholders operating closest to the resources that are being used, require a shift from governing through direct controls to governance where the state interacts with a wide range of interest groups. Although policy seemingly embraces a new water management paradigm, the old is being resurrected with all the contradictions and contortions that precipitated the shift in focus from the old to the new in the first place. There is on the one hand an undeveloped notion of what participation should entail, but there is also a culture in the domain of water that negotiates meanings around technical rather than social discourses. It is the absence of knowledge, the unequal power relationship between water users and the inhibition of agency that makes participation so difficult and keeps those who have knowledge, in - and those who do not have knowledge, out, with the unintended consequence of strengthening bonds between those who have had, in the past, privileged access to water. Those who suffer water deprivation have not been able to use their franchise to improve their access to water and their access to decision-making bodies in the water sector. Repeated failures to achieve reform are costly in terms of finance, and they are costly because they affect the production of trust and make it difficult to retain the 'spirit of the law.' The changing role of the state and the influence that state policy and intervention has in developing or hindering the production of trust and the perpetuation or production of shame is pivotal. Trust is a valuable but volatile resource and the broader set of analytic tools have provided a scafIold using the following set of analytic themes: style of government, way in which bureaucrats accept or resist change, ability of non-state and state actors to develop synergistic relationships, equalising of power, meaningful transfer of knowledge and creation of an agency-enhancing and agency-enabling environment. Trust is a product of a set of 'ideal' conditions, public officials being trustworthy, trading credit slips between water users, having a sense of agency and being able to trust. The ideals of trust present trust as a product of democratic processes and in these ideal conditions trust, as an experience, is reproduced and smoothes relationships. The study expands on the theme of trust by introducing the idea of shame as an inhibitor of trust and examines conditions that activate shame based feelings.